Phytochemical analysis and biological activity of Melastoma malabathricum and Dissochaeta gracilis / Wan Nur Aqilah Wan Mohd Samsudin - Wan Mohd Samsudin, Wan Nur Aqilah (2019)
This study is point out on Thin Layer Chromatography (TLC) profilling, phytochemical analysis, antibacterial activity and antioxidant activity of Melastoma malabathricum and Dissochaeta gracilis. Both of them are belongs to Melastomataceae family. Both samples were extracted by using cold extraction method with different polarity of solvent such as hexane, ethyl acetate and methanol to explore the solvent effect on the percentage yield extraction. TLC profiling was performed by different type of solvent system. Phytochemical analysis was done qualitatively to determine the presence of alkaloids, flavonoids, saponins, phenols, tannins, terpenoids and steroid compounds in all plant samples. Antibacterial activity was analyzing by disc diffusion method using four bacteria such as Staphylococcus aureus, Bacillus subtilis, Salmonella typhi and Escherichia coli. Antioxidant activity was done to determine the percentage of DPPH scavenging of the crude extracts. The results show that methanol crude extract has the highest percentage yield extraction as compared to other crude extracts. Both samples also show best solvent system which is hexane: ethyl acetate with ratio (8:2). The results also determined that steroids, flavonoids and terpenoids has been presence in all extract of both samples. However, they are absence in alkaloid compounds. Meanwhile, M. malabathricum and D. gracilis crude extracts has shown the presence of tannins, saponins and phenol compounds for ethyl acetate and methanol crude extracts but not in hexane crude extract. Apart from that, antibacterial activity show ethyl acetate and methanol crude extract give the higher inhibition of zone against all tested bacteria. Methanol crude extract for D. gracilis show a good free radical scavenging activity with an IC50 value 54.24 µg/ml as compared to M. malabathricum with an IC50 value of 111.90 µg/ml. As conclusion, this study discovered that M. malabathricum and D. gracilis leaves has a great potential as an active antimicrobial and antioxidant agents.